Lithocarpus vuquangensis (Fagaceae), a new species from Vu Quang National Park, Vietnam - Ngoc Nguyen Van; Hung Nguyen Viet; Binh Hoang Thi; Shuichiro Tagane; Hironori Toyama; Hoang Thanh Son; Ha Tran Viet; Tetsukazu Yahara (PhytoKeys, 2018)
Lithocarpus vuquangensis Ngoc & Hung is described from Vu Quang National Park, North Central Vietnam. The morphological comparison and phylogenetic analysis based on rbcL, matK and ITS provided evidence that the new species was not assignable to any of the previously known taxa in Vietnam and its surrounding countries. The description, photographs, preliminary conservation status and DNA barcode sequences are also provided for the new species.